Olmesartan Attenuates Single-Lung Ventilation Induced Lung Injury via Regulating Pulmonary Microbiota - Lu, Di; Wang, Zhizhi; Chen, Zhiming; Fan, Jiayang; Zhai, Jianxue; Fang, Duopei; Cai, He; Liu, Xiguang; Wu, Hua; Cai, Kaican (Frontiers in Pharmacology, 2022)
Single-lung ventilation (SLV) associated acute lung injury is similar to ischemia reperfusion (IR) injury which is usually occurred during lung surgery. Olmesartan (Olm), a novel angiotensin receptor blocker (ARB), has been reported to ameliorate organ IR injury. Several recent studies have shown that lung microbiota may be involved in pulmonary diseases, but the effect of pulmonary microbiota in SLV-induced lung injury has not been reported. This study aims to determine the mechanism of how Olm attenuates SLV induced lung injury. Our data showed that 7 days Olm treatment before modeling markedly alleviated SLV-induced lung injury by suppressing inflammation and reactive oxygen species. Bronchoalveolar lavage fluid samples from the injured side were collected for 16S rRNA gene-based sequencing analysis and 53 different bacteria at the genus and species levels were identified. Furthermore, the injured lung samples were collected for metabolomics analysis using liquid chromatography-mass spectrometry analyses to explore differential metabolites. The Kyoto Encyclopedia of Genes and Genomes (KEGG) was applied to analyze the correlation between differential metabolites and lung microbiota. A total of 38 pathways were identified according to differential metabolites and 275 relevant pathways were enriched via analyzing the microbial community, 24 pathways were both identified by analyzing either metabolites or microbiota, including pyrimidine metabolism, purine metabolism, aminoacyl-tRNA biosynthesis and ATP-binding cassette transporter. Besides classical blockage of the renin-angiotensin II system, Olm could also alleviate SLV-induced lung injury by rewiring the interaction between pulmonary microbiota and metabolites.